STUDI PENJAJARAN ARSITEKTUR MASJID-MASJID TUA DI ACEH DAN DI JAWA PESISIRAN DITINJAU DARI SOSOK, TEKTONIKA, DAN ORNAMENTASI KASUS STUDI MASJID DI ACEH, BANTEN, CIREBON, DEMAK, DAN KUDUS - Gustama, Ridho; Saliya, Yuswadi (Riset Arsitektur (RISA), 2024)
Abstract - Aceh played an important role in the introduction of Islam in Indonesia. Aceh's geographical location on the coast made it one of the cities where traders from all over the world met. Therefore, there are many relationships between Aceh and the cultures that enter Aceh. In addition, Aceh is one of the regions in Indonesia that holds strong Islamic law in social life. Religious buildings, especially mosques in Aceh, are important because they are not only a place of worship but also a place for learning and religious tourism. Ancient mosques in Aceh were found to have similarities with ancient mosques in the Java Coast with the discovery of a sketch of the Baiturrahman Mosque before it was burned. From these discoveries, the research raised the question 'How are the similarities and differences in the architecture of old mosques in Aceh and Coastal Java in terms of Figure, Tectonics, and Ornamentation?' and 'What are the factors that influence the similarities and differences?'. The purpose of this study is to find out the similarities and differences between ancient mosques in Aceh and coastal Java in terms of figure, tectonics, and ornamentation. In addition, to find out the factors that influence the similarities and differences. The study uses a qualitative method where the materials obtained from the field of research are in the form of words and datas that produce descriptive analysis in the form of written and verbal words. As for the studied objects, they are categorized into two categories, namely the jami mosque and the big mosque. Jami mosque consists of Tuha Ulee Kareng Mosque, Tuha Lamura Mosque, Tgk Fakinah Mosque, and Beuracan Mosque. Meanwhile, the big mosque consists of the Indrapuri Mosque. Throughout this research, it was found that the figures of Aceh and Java Coastal Mosques have similarities, while in tectonical aspect there are similarities in the use of the saka guru structural system. Besides similarities, there are differences in tectonical aspects in which the Aceh Mosque is still seen using column binding beams that are visible above the floor while the Java Coastal Mosque does not use them. For ornamentation, the similarities between the Aceh Mosque and Java Coastal Mosque are dominated while the striking difference is the use of memala at the top of the roof whereas the Aceh Mosque does not use memala while the mosque in Java Coastal uses it. In addition, there is an interesting ornamentation in the form of banana heart ornamentation which is found similar to the completion of the ceiling in India (Mughal Era) and similarities with ornaments in the Sunan Gunung Jati Tomb Complex. It was caused by several factors, namely political factors, locality factors, and external factors. Keywords: forms, tectonics, ornamentation, Aceh